Effects of dry needling and stretching exercise versus stretching exercise only on pain intensity, function, and sonographic characteristics of plantar fascia in the subjects with plantar fasciitis: a parallel single-blinded randomized controlled trial. - Salehi, Saman; Shadmehr, Azadeh; Olyaei, Gholamreza; Bashardoust, Siamak; Mir, Seyed Mohsen (Physiotherapy Theory & Practice, 2023)
Plantar fasciitis is a common problem in the foot region which has negative considerable impact on foot function. In this parallel blinded randomized controlled trial, a total of thirty-seven subjects with plantar fasciitis (forty feet) were enrolled randomly to either the control group (stretching exercise) or the experimental group (stretching exercise plus dry needling). All interventions lasted six weeks and both groups were followed for two weeks. Primary outcomes were first step pain, pain, and activity daily function subscales of the FAOS questionnaire and secondary outcomes were plantar fascia thickness, and echogenicity. The mixed model ANOVAs showed significant group × time interactions for all primary outcomes. In both groups, first step pain and both subscales of the FAOS questionnaire were improved compared to baseline measurements. There were considerable differences between the two groups and the experimental group experienced more improvements in primary outcomes compared to the control group. For secondary outcomes, plantar fascia thickness at insertion significantly decreased, and the echogenicity in the two regions significantly increased in the experimental group compared to the control group. These results suggest that the combination of dry needling and stretching exercises can be an effective conservative treatment for plantar fasciitis subjects.